Financial Management Sebagai Variabel Mediasi: Pengaruh Literasi Keuangan Dan Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan UMKM Di Yogyakarta - Davia Mia Amanda; Baldric Siregar; Miswanto Miswanto; Frasto Biyanto (Bajang Institute, 2026)
This study examines the effect of financial literacy and accounting understanding on the financial reporting quality of Micro, Small, and Medium-sized Enterprises (MSMEs) in Yogyakarta, with financial management as a mediating variable. MSMEs play a strategic role in Indonesia's economy, yet many still face challenges in producing quality financial reports. Drawing on the Resource-Based View extended with the dynamic capabilities perspective, this study proposes that cognitive resources such as financial literacy and technical resources such as accounting understanding require operational capabilities in the form of financial management to translate into quality reporting outputs. A quantitative approach was employed through structured questionnaires distributed to 100 MSME actors in Yogyakarta, selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The results indicate that financial literacy positively affects both financial reporting quality (β = 0.302; p = 0.004) and financial management (β = 0.354; p = 0.000). Accounting understanding significantly affects financial management (β = 0.518; p = 0.000) but does not directly affect financial reporting quality (β = -0.070; p = 0.555). Financial management is the strongest predictor of reporting quality (β = 0.616; p = 0.000). Mediation analysis reveals complementary (partial) mediation for financial literacy and indirect-only (full) mediation for accounting understanding. These findings confirm financial management as the pivotal mechanism translating cognitive resources into quality reporting outputs, providing implications for MSME empowerment programs that should integrate conceptual training with operational financial management practices.